Antibodies against Leptospira spp in dairy goats in Guanajuato, Mexico - Luna Álvarez, Miguel Ángel (2018)
The study aimed to determine the serological profile of antibodies against leptospirosis in two dairy goat units in Apaseo el Alto, Guanajuato, Mexico in 2014. Saanen, Alpine, Nubian and Toggenburg goats were classified according to age for random sampling. The microscopic agglutination test (MAT) with live antigen proposed by the World Organisation for Animal Health (OIE) and the World Health Organization (WHO) were used for detecting anti-Leptospira antibodies. Twelve serovars of Leptospira spp were used and animals with equal or higher titres of 1:100 were considered positive. Results showed that 68.3% (41/60) of samples of Unit «A» were positive, with titres from 1:100 to 1: 1600, while 72.4% (97/134) of samples of Unit «B» were positive, with titres between 1:100 to 1:800. Frequencies of positive animals according to age ranged from 20% in kids and 100% in adults. It is concluded that the anti-Leptospira antibodies were high and were generated by an infectious process since the animals were never vaccinated against the disease.